CHARACTERISTICS OF REFINING TECHNOLOGIES FOR VARIOUS VEGETABLE OILS - Djuraev Bakhodir Begaliyevich; Hakimov Baxodir Botir og’li; Isayeva Gulbahor Abdulla qizi (Bright Mind Publishing, 2025)
This article provides a detailed analysis of the specific characteristics and methods of the refining process for various oils. The article examines the main stages such as oil bleaching, deodorization, color alteration, and filtration. The results of this study are of significant importance for the production of high-quality products in the food and chemical industries, contributing to the provision of healthy and safe oils for consumers.
Keywords: Various oils, refining process, rapeseed oil, mustard oil, complex compounds, erucic acid, alkali content, glyceride composition, bleaching earths, fatty acids, sesamolin, sesame oil, hemp oil, whale oil.